The Role of Art in the Interior: Enhancing Spaces with Creativity and Personality - Aliyeva Nasiba Khasanovna (Scientific Trends, 2024)
Art plays a crucial role in interior design, allowing individuals to express their personal style, establish the mood of a room, and elevate the overall visual appeal. Whether it's showcased in a sleek minimalist apartment, a warm and inviting living room, or a grand office lobby, the right artwork has the power to transform an ordinary space into one that is both inspiring and vibrant. This article delves into how art can enhance interior spaces, evoke specific emotions, and infuse personality into homes and work environments.
Keywords: Art, color, interior, creative, design, paint, artwork, effect, contrast, visual.